Knowledge of Maintaining Dental and Oral Health for Pregnant Women in Baki District - Wulandari, Devi; Riolina, Ana; Sari, Morita; Kurniawati, Dwi; Sukini, Sukini (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Physiological processes that occur during pregnancy can cause hormonal changes and affect the oral cavity. Oral problems during pregnancy, such as periodontal disease, gingivitis, tooth erosion, halitosis, and epulis of pregnancy not only impact the mother but can also cause adverse pregnancy outcomes such as premature birth, low birth weight, preeclampsia to premature rupture of membranes. Many pregnant women do not care about the possible adverse effects of dental and oral diseases on pregnancy. This shows that the majority of pregnant women only focus on pregnancy and do not reduce dental and oral health. The occurrence of dental and oral diseases during pregnancy is not only influenced by the pregnancy itself but also the lack of knowledge about maintaining oral health it affects poor behavior in maintaining dental and oral health. The aim of this study was to find out the description of knowledge about maintaining the oral and dental health of pregnant women in Baki District. This research is a type of observational research with a cross-sectional study approach, and quantitative data, and is presented descriptively. The number of respondents in this study was 55 pregnant women in Baki District. Data collection techniques in this study used a questionnaire that had been tested for validity and reliability tests. Research data were analyzed using univariate analysis. The results showed that the proportion of pregnant women's level of knowledge about maintaining oral health was highest in the poor category, which was 69.1% with an average value of knowledge of pregnant women was 6.82. The conclusion of the study is that the level of knowledge regarding maintaining the oral and dental health of pregnant women in Baki District is still lacking.